Meningkatkan Hasil Belajar Pendidikan Agama Katolik Bagi Siswa Kelas VII SMPN 3 Kelam Permai Melalui Materi Peran Keluarga Bagi Perkembanganku dengan Metode Problem Based Learning Tahun Ajaran 2024/2025 - Gaderia Gaderia (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The conditions observed during Catholic Religion lessons for seventh-grade students at SMPN 3 Kelam Permai in the 2024/2025 academic year indicate a lack of concentration among students. They frequently engage in conversations with peers, exhibit limited fluency in articulating their opinions, struggle with analyzing the material being studied, and demonstrate minimal participation in class activities. These factors collectively contribute to suboptimal student learning outcomes. The problem formulation in this study is as follows: How is the Problem-Based Learning (PBL) method applied to the topic "The Role of the Family in My Development" in class VII at SMPN 3 Kelam Permai? Can the implementation of the Problem-Based Learning (PBL) method enhance the learning outcomes of class VII students at SMPN 3 Kelam Permai in the subject of Catholic Religious Education? Additionally, what challenges are encountered in the application of the Problem-Based Learning (PBL) method in teaching Catholic Religious Education in class VII at SMPN 3 Kelam Permai? The research data gathered by the researcher originates from two primary sources: First, the outcomes of observations regarding the Independence of Interest and Motivation of students, conducted by colleagues or derived from the researcher’s own observations during the instructional unit "My Abilities and Limitations," utilizing the Problem Based Learning (PBL) model in class VII at SMPN 3 Kelam Permai during the 2024/2025 Academic Year. Second, the data collection method for assessing the Independence of Interest and Motivation of students involves administering tests at the conclusion of each cycle. Since the pre-cycle research, Cycle I, and Cycle II, students have consistently surpassed the minimum achievement threshold of 70%. In the pre-cycle research, no students fell within the range of 81-100. In Cycle I, four students (21%) achieved scores in the range of 81-100. In Cycle II, nine students (49%) attained scores within the same range.